Großflächige Tracerversuche zum Einfluss von Sohlbaggerungen auf Entwicklung des Grundwassereintrags - Matthias Munz; Daniel Strasser; Hermann-Josef Lensing; Sascha E. Oswald (Grundwasser, 2025)
Zusammenfassung Die an der Schleuse Brandenburg vorherrschenden Potenzialunterschiede führen zu einer permanenten Infiltration von Oberflächenwasser aus dem oberen Vorhafen des Bauwerks in den oberflächennahen Grundwasserleiter, vergleichbar mit den Verhältnissen bei einer Uferfiltration. Durch die geringen Fließgeschwindigkeiten im Oberwasser kommt es zu Ablagerungen von Feinsedimenten, die lokal zu Kolmationshorizonten führen können. Mittels kontinuierlicher Wasserstands- und Temperaturmessungen sowie wiederholten, großflächigen Tracerversuchen wurde untersucht, inwieweit die Störung der potenziellen Kolmationsschicht das Infiltrationsmuster von Oberflächenwasser in den Grundwasserleiter, die Grundwasserstände sowie das Strömungsfeld beeinflusst. Die Entfernung von mehreren Dezimetern schwach toniger, schluffiger Sande durch Sohlbaggerung führte zu keiner relevanten Gesamtänderung des Grundwasserspiegels oder der Grundwassertemperatur. Die detaillierte Auswertung der beiden Tracerversuche vor und nach der Sohlbaggerung zeigt jedoch, dass lokal relevante Veränderungen des Grundwasserströmungsfeldes aufgetreten sind. Durch die eingriffsbedingte Veränderung der dominanten Infiltrationszonen im Oberwasser des Bauwerks wurden die Grundwasserfließwege verkürzt und dadurch Verweilzeiten im Aquifer hin zu Grundwassermessstellen um den Faktor 2,5 reduziert.

Pseudomonas syringae DC3000 infection increases glucosylated N-glycans in Arabidopsis thaliana - Gernot Beihammer; Andrea Romero-Pérez; Daniel Maresch; Rudolf Figl; Réka Mócsai; Clemens Grünwald-Gruber; Friedrich Altmann; Els J. M. Van Damme; Richard Strasser (Glycoconjugate Journal, 2023)
Studying the interaction between the hemibiotrophic bacterium Pseudomonas syringae pv. tomato DC3000 and Arabidopsis thaliana has shed light onto the various forms of mechanisms plants use to defend themselves against pathogen attack. While a lot of emphasis has been put on investigating changes in protein expression in infected plants, only little information is available on the effect infection plays on the plants N-glycan composition. To close this gap in knowledge, total N-glycans were enriched from P. syringae DC3000-infected and mock treated Arabidopsis seedlings and analyzed via MALDI-TOF–MS. Additionally, fluorescently labelled N-glycans were quantified via HPLC-FLD. N-glycans from infected plants were overall less processed and displayed increased amounts of oligomannosidic N-glycans. As multiple peaks for certain oligomannosidic glycoforms were detected upon separation via liquid chromatography, a porous graphitic carbon (PGC)-analysis was conducted to separate individual N-glycan isomers. Indeed, multiple different N-glycan isomers with masses of two N-acetylhexosamine residues plus 8, 9 or 10 hexoses were detected in the infected plants which were absent in the mock controls. Treatment with jack bean α-mannosidase resulted in incomplete removal of hexoses from these N-glycans, indicating the presence of glucose residues. This hints at the accumulation of misfolded glycoproteins in the infected plants, likely because of endoplasmic reticulum (ER) stress. In addition, poly-hexose structures susceptible to α-amylase treatment were found in the DC3000-infected plants, indicating alterations in starch metabolism due to the infection process.

Tiefenorientierte Pumpversuche zur Bestimmung der hydraulischen Anisotropie in einem geschichteten Grundwasserleiter - Ruth Maier; Carsten Leven; Daniel Strasser; Bernhard Odenwald; Olaf A. Cirpka (Grundwasser, 2022)
Zusammenfassung Die horizontale Schichtung von Sedimentkörpern bewirkt, dass die effektive hydraulische Durchlässigkeit eines sedimentären Grundwasserleiters in horizontaler Richtung größer ist als in der vertikalen, was sich unter anderem auf die Ausbreitung des Absenktrichters bei Grundwasserentnahmen auswirkt. Um die großräumige hydraulische Anisotropie zu bestimmen, führten Maier et al. (2022a) an einem Testfeld am Oberrhein tiefenorientierte Pumpversuche mit einem Förderbrunnen mit drei Filterstrecken durch. Die Grundwasserentnahmen erfolgten nacheinander jeweils aus einer Tiefe. Die Absenkungen aller Versuche wurden in verschiedenen Abständen zum Förderbrunnen und verschiedenen Tiefen gemessen und gemeinsam mit einem Computermodell ausgewertet. In der vorliegenden Arbeit zeigen wir, dass die Interpretation von Absenkkurven bei Entnahme aus nur einer Tiefe zu Durchlässigkeitsbeiwerten führt, die vornehmlich die Bedingungen in der Entnahmetiefe widerspiegeln. Für die Bestimmung vertikaler Unterschiede der hydraulischen Durchlässigkeit und der hydraulischen Anisotropie ist es notwendig, Versuche mit mehreren Entnahmetiefen zu kombinieren. Der Arbeitsaufwand im Feld kann jedoch durch eine optimierte Beobachtungsstrategie reduziert werden.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Revealing vertical aquifer heterogeneity and hydraulic anisotropy by pumping partially penetrating wells - Ruth Maier; Carsten Leven; Emilio Sánchez-León; Daniel Strasser; Maximilian Stoll; Olaf A. Cirpka (Hydrogeology Journal, 2022)
The stratification of sedimentary aquifers introduces spatial variability in hydraulic conductivity, primarily between individual horizontal layers. On larger scales, the vertical heterogeneity enhances hydraulic anisotropy, with the horizontal conductivity typically exceeding the vertical one. In this study, the hydraulic anisotropy of a stratified aquifer is estimated from data of hydraulic tests in which water is sequentially extracted from well sections screened at different depths, and the hydraulic response is measured at various multilevel observation wells. The applicability of the method is demonstrated by field tests in a fluvial gravel aquifer in the Upper Rhine Valley, Germany. A homogeneous anisotropic model, and models with three and five anisotropic layers, are fitted to the measured drawdowns in the steady-shape regime, in which differences in hydraulic head between observation locations do not change over time even though the head values themselves change. The position of the five horizontal layers is based on the lithology of the drilling profile at the pumping-well location. The three-layer model is achieved by merging insensitive or similar layers with sensitive layers. The fits result in estimates of the radial and vertical hydraulic conductivities for all layers of the respective models, which are upscaled to effective parameters over the entire depth in the case of the multilayer models. The homogeneous model shows significantly higher errors than those of the heterogeneous models. The heterogeneous locally anisotropic models not only reveal vertical variability of hydraulic conductivity, but also lead to a three-times larger anisotropy ratio upon upscaling.

Correction: Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)

Correction: Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)

Impact of river reconstruction on groundwater flow during bank filtration assessed by transient three-dimensional modelling of flow and heat transport - Wei-shi Wang; Sascha E. Oswald; Thomas Gräff; Hermann-Josef Lensing; Tie Liu; Daniel Strasser; Matthias Munz (Hydrogeology Journal, 2020)
Bank filtration (BF) is an established indirect water-treatment technology. The quality of water gained via BF depends on the subsurface capture zone, the mixing ratio (river water versus ambient groundwater), spatial and temporal distribution of subsurface travel times, and subsurface temperature patterns. Surface-water infiltration into the adjacent aquifer is determined by the local hydraulic gradient and riverbed permeability, which could be altered by natural clogging, scouring and artificial decolmation processes. The seasonal behaviour of a BF system in Germany, and its development during and about 6 months after decolmation (canal reconstruction), was observed with a long-term monitoring programme. To quantify the spatial and temporal variation in the BF system, a transient flow and heat transport model was implemented and two model scenarios, ‘with’ and ‘without’ canal reconstruction, were generated. Overall, the simulated water heads and temperatures matched those observed. Increased hydraulic connection between the canal and aquifer caused by the canal reconstruction led to an increase of ~23% in the already high share of BF water abstracted by the nearby waterworks. Subsurface travel-time distribution substantially shifted towards shorter travel times. Flow paths with travel times <200 days increased by ~10% and those with <300 days by 15%. Generally, the periodic temperature signal, and the summer and winter temperature extrema, increased and penetrated deeper into the aquifer. The joint hydrological and thermal effects caused by the canal reconstruction might increase the potential of biodegradable compounds to further penetrate into the aquifer, also by potentially affecting the redox zonation in the aquifer.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Modeling the Effect of the Selective S1P1 Receptor Modulator Ponesimod on Subsets of Blood Lymphocytes - Dominik Lott; Andreas Krause; Christian A. Seemayer; Daniel S. Strasser; Jasper Dingemanse; Thorsten Lehr (Pharmaceutical Research, 2017)

Sediment dynamics and geohazards off Uruguay and the de la Plata River region (northern Argentina and Uruguay) - Sebastian Krastel; Gerold Wefer; Till J. J. Hanebuth; Andrew A. Antobreh; Tim Freudenthal; Benedict Preu; Tilmann Schwenk; Michael Strasser; Roberto Violante; Daniel Winkelmann (Geo-Marine Letters, 2011)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Sialic acid concentrations in plants are in the range of inadvertent contamination - Reinhard Zeleny; Daniel Kolarich; Richard Strasser; Friedrich Altmann (Planta, 2006)